Standalone track reconstruction on GPUs in the first stage of the upgraded LHCb trigger system & Preparations for measurements with strange hadrons in Run 3 - Calefice, Lukas (Technische Universität Dortmund, 2022)
The LHCb experiment is undergoing its first major detector upgrade to operate at a five times higher instantaneous luminosity during the Run 3 data taking period. It is equipped with a new set of tracking detectors (VELO, UT, SciFi) to match the conditions of an increased track multiplicity and radiation damage. The hardware trigger stage is removed. The first stage of the software trigger system is implemented to run on about 200 GPU cards with a throughput of 30MHz. An alternative tracking algorithm called Seeding & Matching for the first trigger stage is developed and presented in this thesis. Other than the formerly used forward tracking, the presented algorithm performs the tracking without making use of the UT which allows to run in the early data taking of Run 3 before the UT will be installed. The Seeding is a standalone reconstruction of track segments in the SciFi, which is followed by a Matching step where the SciFi seeds are matched to VELO track segments reconstructed beforehand. The physics and computing performance of the Seeding & Matching is evaluated and found to be compatible with the forward tracking. The Seeding & Matching is now used as the new baseline algorithm and currently being commissioned on the first Run 3 data. Furthermore, preparations for an early Run 3 measurement of the ratios of the production cross-section of Λ and KS hadrons are presented in this thesis.

L'expérience LHCb au CERN est en train d'effectuer son premier majeur upgrade (LHCb) afin de pouvoir prendre des données avec une luminosité cinq fois plus grande pendant le Run 3. Il sera équipé d'un nouvel ensemble de trajectographes (VELO, UT, SciFi) pour s'adapter aux conditions d'une multiplicité de traces et d'un rayonnement plus élevée. La première étape du système de trigger est mise en œuvre pour fonctionner sur 200 cartes GPU à un débit de données de 30MHz. Une reconstruction de trace alternative, appelée Seeding & Matching, pour le premier niveau du trigger est développée et présentée dans cette thèse. Contrairement au forward tracking utilisé précédemment, l'algorithme présenté ici se passe de l'UT, de sorte qu'il peut être utilisé avant que l'UT ne soit complètement installé. Le Seeding est une reconstruction autonome de segments de trace dans le SciFi, suivie d'un Matching où les segments du SciFi sont associés aux segments de trace VELO reconstruits précédemment. Le Seeding & Matching montre une performance physique et informatique compatible avec le forward tracking. Il est maintenant utilisé comme nouvel algorithme principal et mis en service avec les premières données du Run 3. De plus, des études préparatoires pour une mesure avec les premières données du Run 3 LHCb des rapports des sections efficaces de production des hadrons Λ et KS sont présentées dans cette thèse.

Das LHCb-Experiment durchläuft sein erstes großes Detektor-Upgrade, um während Run 3 Daten mit einer verfünffachten instantanen Luminosität nehmen zu können. Es wird dafür mit einem neuen Satz an Spurfindungsdetektoren (VELO, UT, SciFi) ausgestattet, um sich an die Bedingungen der erhöhten Spurmultiplizität und Strahlungsschäden anzupassen. Der Hardware-Trigger wird entfernt. Die erste Stufe des Software-Triggers ist implementiert um auf 200 GPU-Karten bei einem Datendurchsatz von 30 MHz zu laufen. Eine alternative Spurrekonstruktion, genannt Seeding & Matching, für die erste Triggerstufe wird entwickelt und ist präsentiert in dieser Arbeit. Im Gegensatz zu dem vorher verwendeten forward tracking kommt der hier präsentierte Algorithmus ohne den UT aus, sodass er am Anfang von Run 3 verwendet werden kann bevor der UT vollständig installiert ist. Das Seeding ist eine eigenständige Rekonstruktion von Spursegmenten im SciFi, auf die ein Matching folgt, wo die SciFi-Segmente den vorher rekonstruierten VELO-Spursegmenten zugeordnet werden. Das Seeding & Matching zeigt ein physikalische und Computing- Performance kompatibel mit dem forward tracking. Es wird momentan als neuer Hauptalgorithmus verwendet und mit den ersten Run 3 Daten in Betrieb genommen. Zusätzlich werden vorbereitende Studien für eine Messung mit ersten Run 3 LHCb- Daten von Verh ̈altnissen der Produktionswirkungsquerschnitte von Λ0 und KS0 Hadronen in dieser Arbeit vorgestellt.
Keywords: Real-time analysis; Track reconstruction; LHCb upgrade; GPUs; LHCb; 530; LHCb <Teilchendetektor>; Upgrade; Echtzeit; Datenanalyse